2017
DOI: 10.1039/c7ra00586e
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of highly oriented poly(vinylidene fluoride) uniform films and their ferro- and piezoelectric properties

Abstract: Uniform active films are highly desirable for electronic applications, but still challenging. This work proposed a convenient and effective approach for the production of uniform oriented PVDF thin films with high content of polar b-phase by blade shear. The obtained films not only had a smooth surface, but also achieved uniform component distribution. The results revealed that PVDF crystals preferentially oriented perpendicular to the shear direction and the largest relatively b-phase content was up to 93% ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…In fact, the α-phase has characteristic peaks at around 803 cm -1 , whereas the β-phase gives a peak at 848 cm -1 . Also in this case, from the intensities of these two contributions, it is possible to estimate the ratio between the βand α-phase in the sample [38]. In agreement with FTIR, Raman spectroscopy highlights a significant increase of the β-phase in PNPs (β/α = 3), as compared to P(VDF-TrFE) powder (β/α = 2).…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…In fact, the α-phase has characteristic peaks at around 803 cm -1 , whereas the β-phase gives a peak at 848 cm -1 . Also in this case, from the intensities of these two contributions, it is possible to estimate the ratio between the βand α-phase in the sample [38]. In agreement with FTIR, Raman spectroscopy highlights a significant increase of the β-phase in PNPs (β/α = 3), as compared to P(VDF-TrFE) powder (β/α = 2).…”
Section: Resultsmentioning
confidence: 55%
“…Both bulk P(VDF-TrFE) and PNPs FTIR spectra present the peculiar peaks at 842 and 1279 cm -1 , corresponding to the β-phase of the polymer. The typical peaks of the α-phase arrangement (610, 765, 965 cm -1 ) are very weak and extremely difficult to identify, especially for PNPs (Figure 2c) [38]. This suggests that the polymer preferentially crystallizes in the β-phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the characteristic bands of the α-phase [ 51 ] (854, 975, 1149, 1209, 1383 and 1423 cm −1 ) are weak or located below (410, 489, 532, 614, 763, 795 cm −1 ) the lower limit of our apparatus, which is given by the Ge crystal used. Thus, the fractions of a particular PVDF phase cannot be estimated by the generally accepted approach [ 51 , 53 , 54 , 55 ] based on the α-phase peak at 763 cm −1 . In order to calculate the relative percentage of γ- and β-phases we consider the number of electroactive phases consist only of γ- and β-phases (100%) and use the peak to valley method [ 51 ]: valley of ~1276 cm −1 and peak of 1260 cm −1 for β-phase and valley of ~1232 cm −1 and peak of 1225 cm −1 for γ-phase.…”
Section: Resultsmentioning
confidence: 99%
“…Commonly, phase analysis in literature consists of the intensity ratio of the α and β phase peaks, resulting in a value of zero for pure β phase or infinity for pure α phase. 53,60 To quantify the relative phase content of the β and ɣ phases in the SWCNT/PVDF-TrFE (0.000 wt% to 0.500 wt%) films, a series of equations were used in this study and are shown in eqn (3) and (4), respectively.…”
Section: Phase Determination and Materials Propertiesmentioning
confidence: 99%